2018
DOI: 10.5301/tj.5000653
|View full text |Cite
|
Sign up to set email alerts
|

Association of MNS16A VNTR and hTERT rs2736098: G>A polymorphisms with susceptibility to diffuse large B-cell lymphoma

Abstract: MNS16A genetic variations are associated with DLBCL susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The polymorphic number of MNS16A tandem repeats was reported to be associated with the risk of several malignancies, including lung24,47 or colorectal and prostate cancer,38,39 malignant gliomas,40,41 as well as Alzheimer’s disease 48. So far, the MNS16A VNTR polymorphism of the hTERT catalytic subunit has been described in two lymphoproliferative disorders: first in our study on NHL, 27 and later in diffuse large B-cell lymphoma (DLBCL) 49. Our previous work identified some relationships between the VNTR-243 variant with more aggressive disease and with less favorable response to therapy 27.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The polymorphic number of MNS16A tandem repeats was reported to be associated with the risk of several malignancies, including lung24,47 or colorectal and prostate cancer,38,39 malignant gliomas,40,41 as well as Alzheimer’s disease 48. So far, the MNS16A VNTR polymorphism of the hTERT catalytic subunit has been described in two lymphoproliferative disorders: first in our study on NHL, 27 and later in diffuse large B-cell lymphoma (DLBCL) 49. Our previous work identified some relationships between the VNTR-243 variant with more aggressive disease and with less favorable response to therapy 27.…”
Section: Discussionmentioning
confidence: 55%
“…Our previous work identified some relationships between the VNTR-243 variant with more aggressive disease and with less favorable response to therapy 27. The study on DLBCL revealed that Egyptian carriers of the S allele or the SS genotype of MNS16A were at higher risk of disease development 49. Wang et al investigated promoter activity of MNS16A VNTRs in lung cancer cells and showed that the shorter VNTR (S) variant correlated with lower promoter activity, while the longer VNTR (L) was associated with increased risk of lung cancer 24.…”
Section: Discussionmentioning
confidence: 99%
“…Mature B‐cell lymphoma is collectively the 10th most common cancer worldwide, with nearly 386,000 new diagnoses annually (2012 Cancer Research UK statistics), and of these 40% are DLBCL. In recent years, many studies have confirmed that genetic factors, especially the single nucleotide polymorphism (SNP), are closely associated with the susceptibility of DLBCL …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have confirmed that genetic factors, especially the single nucleotide polymorphism (SNP), are closely associated with the susceptibility of DLBCL. [2][3][4] MicroRNAs (miRNAs) are 17 to 25-nucleotide noncoding RNAs that can modulate the expression of target genes. Accumulating evidence has shown that miRNA might play critical roles in cancer initiation and the progression processes, 5 including DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…rs2736098 has been suggested to be significantly associated with carcinogenesis in multiple tissues besides breast, including lung, basal cell, bladder, prostate, cervix, liver, pancreas, colon, ovary, B cell, head and neck [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Further search in GWAS Catalog, UK BioBank ( https://www.ukbiobank.ac.uk ) and FinnGen ( https://www.finngen.fi/fi ) indicate that rs2736098 is also significantly associated with count of platelet, red and white blood cell, neutrophil, basophil neutrophil and monocyte (all P < 5 × 10 −8 ; results not shown) [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%